1996
DOI: 10.1016/0014-2921(95)00127-1
|View full text |Cite
|
Sign up to set email alerts
|

Politics and the effectiveness of foreign aid

Abstract: Critics of foreign aid programs have long argued that poverty reflects government failure. In this paper I analyze the effectiveness of foreign aid programs to gain insights into political regimes in aid recipient countries. My analytical framework shows how three stylized political/economic regimes labeled egalitarian, elitist and laissez-faire would use foreign aid. I then test reduced form equations using data on nonmilitary aid flows to 96 countries. I find that models of elitist political regimes best pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
520
4
27

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,015 publications
(577 citation statements)
references
References 32 publications
26
520
4
27
Order By: Relevance
“…Ogaki et al, 1996). This suggests, consistent with the evidence cited above, that taxes are unlikely to have exerted ®rst-order eects on African growth via aggregate capital accumulation, the channel emphasized by Boone (1996) and McGuire and Olson (1996). More fundamentally, the African political economy literature has for at least two decades ± certainly since Bates (1981) and the infamous``Berg Report'' of the World Bank (1981) ± grappled with the reality of policy regimes that impose highly dierentiated tax rates on investment, variously favoring public investment over private, urban over rural, foreign (capital¯ight) over domestic, non-traded over traded, or informal over formal (e.g.…”
Section: Introductionsupporting
confidence: 74%
“…Ogaki et al, 1996). This suggests, consistent with the evidence cited above, that taxes are unlikely to have exerted ®rst-order eects on African growth via aggregate capital accumulation, the channel emphasized by Boone (1996) and McGuire and Olson (1996). More fundamentally, the African political economy literature has for at least two decades ± certainly since Bates (1981) and the infamous``Berg Report'' of the World Bank (1981) ± grappled with the reality of policy regimes that impose highly dierentiated tax rates on investment, variously favoring public investment over private, urban over rural, foreign (capital¯ight) over domestic, non-traded over traded, or informal over formal (e.g.…”
Section: Introductionsupporting
confidence: 74%
“…Likewise, Pillai [1982] found that 60% of foreign aid in Jordan was used to finance investment while the remaining 40% was used either to reduce taxes or slacken revenue collection. Boone [1996] overturned the positive results of Dowling and Hiemenz [1982] and Levy [1988] by using instrument techniques and panel data. He finds that foreign aid has no impact on investment and economic growth.…”
Section: Foreign Aid As An Obstacle To Economic Growthmentioning
confidence: 61%
“…The coefficient of aid as a percent of GDP is negative but not significant at the conventional level. The effect of aid on growth may not be linear as suggested by Boone [1996]. There are several reasons for expecting a non-linear relation between aid and growth.…”
Section: Aid and Economic Growth: The Empirical Resultsmentioning
confidence: 87%
“…Moreover, aid could have the effect of worsening investment incentives as it could signal the need for aid in the future (arguably, a situation of moral hazard). In either case, aid would finance consumption rather than investment (Boone, 1996). Similarly, Burnside and Dollar's finding that aid increases growth under good policy environments shows that aid will not necessarily lead to investment.…”
Section: Endogenous Growth Modelsmentioning
confidence: 98%